General characterization and ionization-recombination properties of electronegative elements present in plasma discharges at plasma current switch operation. Part I - Skibenko, E.I.; Yuferov, V.B.; Ozerov, A.N.; Buravilov, I.V. (Вопросы атомной науки и техники, 2021)
Based on literary sources, we present here the data on electron affinity values for a variety of negative atomic ions, and also, for some molecules and radicals being of interest for current experimental studies. Besides, the ionization potentials are given for nearly all ionization states of some electronegative elements (C, O, F, Cl). For the said elements, the ionization-recombination parameters and the dependences of the fractional values (ionic fraction) for ionization states and on the electron temperature within the framework of ionization equilibrium are given. A comparison is carried out between the calculated and experimental distributions of the fractions of multicharged C⁺⁴ ions versus electron temperature. На основі літературних джерел наведені дані по величинам спорідненості до електрону для ряду негативних атомарних іонів і для деяких молекул і радикалів, що представляють інтерес для експериментальних досліджень, що проводяться. Наведено також потенціали іонізації майже за всіма іонізаційними станами для деяких електронегативних елементів (C, O, F, Cl). Для них же наведені іонізаційно-рекомбінаційні параметри і залежності фракційних значень (ionic fraction) по іонізаційним станам від температури електронів у рамках іонізаційної рівноваги (ionization equilibria). Проведено порівняння розрахункових і експериментальних даних за розподілом частки багатозарядних іонів С⁺⁴ від температури електронів. На основе литературных источников приведены данные по величинам сродства к электрону для ряда отрицательных атомарных ионов и для некоторых молекул и радикалов, представляющих интерес для проводимых экспериментальных исследований. Приведены также потенциалы ионизации почти по всем ионизационным состояниям для некоторых электроотрицательных элементов (C, O, F, Cl). Для них же приведены ионизационно-рекомбинационные параметры и зависимости фракционных значений (ionic fraction) по ионизационным состояниям от температуры электронов в рамках ионизационного равновесия (ionization equilibria). Проведено сравнение расчетных и экспериментальных данных по распределениям доли многозарядных ионов С⁺⁴ от температуры электронов.